Image-type representation: A preliminary study on preferences of users with intellectual disabilities. Issue 110 (February 2018) - Rocha, Tânia; Bessa, Maximino; Bastardo, Rute; Magalhães, Luís
Highlights: A study on user's with intellectual disabilities preferences for image-type representation, which can be used in a digital navigation context, is presented Image representation was design according to three types of representation (object (simpler to decoding), action and universe (complex to decoding). Participants with intellectual disabilities preferred objects representative images for the four categories tested (music, sports, games, movies). Abstract: Previous findings have shown that users with intellectual disabilities navigate the Web more easily and with greater interest when images are used to represent hyperlinks (Rocha, 2008; 2014; Rocha et al., 2012). Although images can be better for navigation purposes, there is a need to understand how these images should be designed to enhance users' interaction with digital content for this particular group of people. The purpose of this study is to measure the user's preference for image-type representation (Object, Action and Universe), within four different categories (music, movies, sports, games). The sample consisted of 20 individuals with intellectual disabilities, their ages ranging from 22 to 49 years old. The results showed that they preferred less complex images, namely object representative images, and that categories had no effect.